2015
DOI: 10.1017/s0714980815000392
|View full text |Cite
|
Sign up to set email alerts
|

Perception et réceptivité des proches-aidants à l’égard de la vidéosurveillance intelligente pour la détection des chutes des aînés à domicile

Abstract: To address the issue of falls, which are increasing as the population ages, an intelligent video-monitoring system is being developed. The aim of the study is to explore caregivers' perceptions of and receptiveness to a prototype of this fall detection system. A cross-sectional mixed-method study was carried out with individual interviews of 18 caregivers. Statistical frequencies and content analysis were conducted (SPSS and N'Vivo). The results show that most participants (n = 15/18) liked the intelligent vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The participants' positive perception of the IVS is consistent with previous studies [Lapierre et al, 2015;Londei et al, 2009]. This supports both the value of user-based technology design and studies exploring potential users' perceptions before a technology is developed.…”
Section: Participants' Perception and Implementation Considerationssupporting
confidence: 86%
See 3 more Smart Citations
“…The participants' positive perception of the IVS is consistent with previous studies [Lapierre et al, 2015;Londei et al, 2009]. This supports both the value of user-based technology design and studies exploring potential users' perceptions before a technology is developed.…”
Section: Participants' Perception and Implementation Considerationssupporting
confidence: 86%
“…Indeed, without the Mathematica© software (which is replaceable by freeware), the IVS costs CAN$480. Privacy concerns raised in the literature (Comiskey et al, 2018) were mentioned by two participants, but they were not a barrier in this study or the previous ones [Lapierre et al, 2015;Londei et al, 2009]. This suggests that the IVS's image processing and its closed-circuit functioning might be promising ways of addressing the privacy issue.…”
Section: Participants' Perception and Implementation Considerationsmentioning
confidence: 54%
See 2 more Smart Citations
“…It also stores images from the minutes leading up to the event for analysis. Studies on potential users’ perception of the IVS at home showed that 87 per cent (n = 30) of older people, 43 83 per cent (n = 18) of family caregivers, 44 and most healthcare professionals/managers (n = 31) were in favour of it. 45 However, the IVS was not developed for NHs or implemented in this type of setting.…”
Section: Introductionmentioning
confidence: 99%